ΜΑΙΡΗ ΜΙΚΕ, Τα δάκρυα της πέτρας. Λογοτεχνικές αναπλάσεις του μύθου της Νιόβης - Μικέ, Μαίρη (Σύγκριση/Comparaison/Comparison, 2022)
The tears of stone. Literary transformations of the myth of Niobe The aim of this essay is the study of recreations and transformations of the myth of Niobe and Niobidae in modern Greek literary texts of the end of 19th and 20th centuries. The research of the sources place the poetry in one primary position: a lot of poets (e.g. Palamas, Markoras, Varnalis, Ritsos) and one novelist (T. Athanasiadis) recreate the basic thematic lines of the myth and insist on divisions between life and death, loss and revengeful mania, deadening figure and living impetuous emotion or even more to redemptive petrifaction. As the metamorphoses of the myth of Niobe, at least the most of them, are revolved round the maternal grief and the plea, the focus and the insistence on human insult are cancelled. Niobe - and the poet who suffers along with her – as is not arrogant but just sorrowful, is able, for example, to transform her accumulated grief into love, to search in existential surroundings the revival through the erotic desire or/and thematize the power of art for the achievement of her presence in the long duration of time. From this aspect, a signifying displacement is noticed: by projecting a distressed human existence the divine presence is confined only indirectly, that is from the consequences of the relentless punishment.